(untitled) (World Bulletin of Public Health, 2023)
This article widely covers the scientific and theoretical foundations for the preparation and optimization of management decisions, studies and analyzes the state of preparation and optimization of management decisions at enterprises in the digital economy, and also makes proposals for making and optimizing management decisions. presented